BECARE (PERCERAIAN) ANTARA SUAMI ISTERI MENURUT MASYARAKAT ADAT DAYAK KANAYATN DI DESA KOREK KECAMATAN SUNGAI AMBAWANG KABUPATEN KUBU RAYA - NIM. A1011191263, ALAM PRIMA YUDISTIRA (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract The Dayak Kanayatn Indigenous Community adheres to the provisions of customary law that apply as a guide in regulating the social life of its community, one of which is the Customary Divorce. Customary divorce in Korek Village, Sungai Ambawang District, Kubu Raya Regency is still carried out until now and has been carried out from generation to generation and inherited from the ancestors of the Dayak Kanayatn tribe. At present, there have been changes in customary materials in the settlement of Dayak Kanayatn customary divorce in Korek Village, Sungai Ambawang District, Kubu Raya Regency due to the development of the increasingly advanced life of its community. The formulation of the problem is